Evaluation of the toxic activity of Zinnia peruviana products - Mohamed, Ana Mariel (2024)
Although plants have been used in popular medicine for ages, their safety is often not well studied, and many can be toxic. In this study, the toxicity of Zinnia peruviana products was evaluated through cytotoxicity and genotoxicity assays. Neutral Red (NR) uptake and MTT reduction were used to measure cell growth inhibition by these products. Genetic damage was evaluated using the comet assay. Acetonic extracts of roots, leaves and flowers and ziniolide (major metabolite of the roots extract), were evaluated. The flowers and roots extracts, as well as the ziniolide did not present significant cytotoxic effects on Vero cells using neutral red and MTT assays (CC50> 20 µg/mL). These products also did not cause DNA damage at the lowest concentration tested (0.156 mg/mL). Significant genotoxic damage was observed at concentrations equal to or greater than 1.25 mg/mL, following a dose-dependent behavior. However, the leaves extract showed cytotoxic activity with NR and MTT (CC50 = 18 µg/mL and CC50= 15 µg/mL respectively) and also genotoxicity at low concentration evaluated in previous studies. The results of this research are promising for advancing studies in search of the bioapplicability of these natural compounds as antimicrobial agents.